A Discoidal diorama as an examination of my quarter-life crisis - Meneses, Leticia Fortuna Francia; Cabangis, Benjamin; Romero, Riza A. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2021)
Upon turning thirty, I would come to realize that I'm going through what is called the "quarter-life crisis". Relatively new, this phenomenon had just been coined in the 90's by authors Abby Wilner and Alexandra Robbins. The quarter-life crisis describes shared experiences among people in their mid-twenties to late thirties. My quarter-life crisis realizations served as inspiration for my automated moving sculpture. The objective is to create a diorama to examine my quarter-life crisis; to analyze the phases of my life in a combined literal and metaphorical approach to produce a cohesive visual and personal narrative.

The mixed media diorama is presented in a metal discoid measuring two feet in circumference, atop a metal stand - totaling 6 feet in height. In the diorama my life is metaphorically "quartered" in four stages, symbolized by miniature figures made of epoxy, plastic rhinestones, and plastic toys. The discoid is electrically automated to slowly rotate clockwise, influenced by philosopher Friedrich Nietsche's "eternal reccurence" (what has happened will happen again") and the Filipino belief in "gulong ng palad" (the wheel of fate). The dioramas merge imagery of my four life stages with the four life cycles of the moth, an insect that Virginia Woolf related to human mortality. Guided by Aristotle's four causes, the dioramas were quartered accordingly: childhood and eggs are the material cause while adolescence and larvae are the formal cause. Adulthood and pupae are the efficient cause and lastly, old age and moth are the final cause. These interconnections create meaningful allegories in the sculptural representation of my life in quarters. A discoidal diorama as an examination of my quarter-life crisis was both an artistic, personal journey of self-discovery, and my firm acknowledgement that this phenomenon indeed exists and is a valid part of adult life.
Appendix: leaves 35-37
Thesis (Bachelor of Fine Arts in Studio Arts)
Bibliography: leaves 20-24
Keywords: Diorama; Worry in adolescence; Adolescent analysis